Bordetella bronchiseptica promotes adherence, colonization, and cytotoxicity of Streptococcus suis in a porcine precision-cut lung slice model. Issue 1 (1st January 2021) - Vötsch, Désirée; Willenborg, Maren; Baumgärtner, Wolfgang; Rohde, Manfred; Valentin-Weigand, Peter
ABSTRACT: Bordetella (B.) bronchiseptica and Streptococcus (S.) suis are major pathogens in pigs, which are frequently isolated from co-infections in the respiratory tract and contribute to the porcine respiratory disease complex (PRDC). Despite the high impact of co-infections on respiratory diseases of swine (and other hosts), very little is known about pathogen-pathogen-host interactions and the mechanisms of pathogenesis. In the present study, we established a porcine precision-cut lung slice (PCLS) model to analyze the effects of B. bronchiseptica infection on adherence, colonization, and cytotoxic effects of S. suis . We hypothesized that induction of ciliostasis by a clinical isolate of B. bronchiseptica may promote subsequent infection with a virulent S. suis serotype 2 strain. To investigate this theory, we monitored the ciliary activity by light microscopy, measured the release of lactate dehydrogenase, and calculated the number of PCLS-associated bacteria. To study the role of the pore-forming toxin suilysin (SLY) in S. suis -induced cytotoxicity, we included a SLY-negative isogenic mutant and the complemented mutant strain. Furthermore, we analyzed infected PCLS by histopathology, immunofluorescence microscopy, and field emission scanning electron microscopy. Our results showed that pre-infection with B. bronchiseptica promoted adherence, colonization, and, as a consequence of the increased colonization, the cytotoxic effects of S. suis, probably by reduction of the ciliary activity. Moreover, cytotoxicity induced by S. suis is strictly dependent on the presence of SLY. Though the underlying molecular mechanisms remain to be fully clarified, our results clearly support the hypothesis that B. bronchiseptica paves the way for S. suis infection.